Sustainable forest ecosystem management - rangra, Nishant; Xu, Haibo (Open Science Journal, 2024)
Development in forest management focuses on property forest scheme management that collaborates with the surroundings socially, economically, and culturally. A continuation within the provider of timber is on the market by property forest scheme management. The most aim of property forest management is to keep up a healthy environmental society and to guard the diverseness for our future diversity. On the opposite hand, the property forest scheme emphasizes safeguarding and managing the scheme of the forest. Management emphasizes the methods that square measure was taken by property forest scheme management to guard the life within the forests to stay growing the trees of the forests naturally. In the given paper it is been discussed that awareness of the environmental, economic, and social relevance and worth of the Carpathian Mountains' forests, a natural legacy that may be a reliable component. The study has used a comparative study of the key trends and techniques in current sustainable forest management to strengthen the theoretical and methodological basis. The paper has also included the few of the major challenges faced by the maintenance sector of forest ecosystem. Several sustainable forestry methods can help forests regenerate or protect them. They include erecting a fence to keep deer out, managing weeds and other vegetation, and cutting trees to enable more sunlight to reach the forest floor. Hence, the major goal was to show how crucial ecosystem services supplied all across these protected areas are for long-term local and national ecosystem development.